A missense mutation in PDHB gene: identification of the patient with pyruvate dehydrogenase deficiency and demonstration of pathogenicity in vitro - Ying Li; Lin Cheng; Xin Li; Jiyu Liu; Lu Yi; Tao Bo (Italian Journal of Pediatrics)
Abstract Background Pyruvate dehydrogenase (PDH) deficiency is an uncommon condition responsible for primary refractory lactic acidosis, and PDH E1β (PDHB) subunit gene mutation rarely causes of PDH deficiency. We described a missense mutation of PDHB gene in a neonate with PDH deficiency, and verified the mutation damages PDH activity in vitro. Methods Whole exome sequencing (WES) was used to discover the missense mutation. We constructed the recombinant eukaryotic recombinant expression vector, the phage-PDHB-wt/mut, containing human full-length wild-type (NM_000925.4) or mutant (c.575G > T) PDHB gene, and transfected vector into 293T cells. Western blot was performed to assess PDH protein stability, PDH activity was measured. Results A 37-week-gestation male infant was noted to have refractory lactic acidosis, growth retardation, and neurodevelopmental anomalies with abnormal brain magnetic resonance (MR) findings, starting with convulsive seizures at 3 months of age. WES analysis revealed the homozygous missense mutations in the PDHB gene, which was c.575G > T (p.Arg192Leu) in exon 6. This missense mutation of PDHB was predicted to be harmful by bioinformatics software including Sorting Intolerant From Tolerant (SIFT), Polyphen2, LRT, and Mutation Taster. Western blot showed that normal PDH protein expression was significantly decreased in the phage -PDHB-mut transfected cells than that in the phage -PDHB-wt transfected cells (P < 0.001). PDH activities analysis revealed that PDH activity was significantly decreased in the phage -PDHB-mut transfected cells than that in the phage -PDHB-wt transfected cells (P < 0.001). Conclusions c.575G > T (p.Arg192Leu) in PDHB gene is a pathogenic missense mutation, which causes PDH deficiency in autosomal recessive inheritance mode.